Simplified Cable Nerve Grafting with Nerve-Cutting Guides and Fibrin Glue - Draeger, Reid W.; Bynum, Donald K., Jr.; Patterson, J. Megan M. (Journal of Hand and Microsurgery, 2017)
Cable nerve grafting is the recommended surgical treatment for large peripheral nerve defects. Traditionally, this is performed by bridging a gap in the nerve with multiple autologous nerve cables, repairing the epineurium of each cable to the perineurium of a fascicle of the injured nerve that is similar in size to the graft. The authors present a new technique in which they used nerve-cutting guides to aid in the placement of fibrin glue to secure the sides of the cabled nerve graft together to facilitate handling of the cabled nerve graft and to expedite repair. Freshening the graft nerve ends after the application of fibrin glue using appropriately sized nerve-cutting guides allows for donor-recipient size match and epineurium-to-epineurium repair of the cabled graft to injured nerve. Though further follow-up is needed to determine long-term outcomes following this technique, early results are promising with clinical improvement seen in a similar timeframe to traditional grafting.
Keywords: cable nerve grafting; fibrin glue; nerve-cutting guide